Occupational exposure to silica and risk of heart disease: a systematic review with meta-analysis - Kai Liu; Min Mu; Kehong Fang; Yuanyuan Qian; Song Xue; Weijiang Hu; Meng Ye (BMJ Open, 2020)
Objective To search for evidence of the relationship between occupational silica exposure and heart disease.Design A systematic review and meta-analysis.Background Growing evidence suggests a relationship between occupational silica exposure and heart disease; however, the link between them is less clear.Data sources PubMed, ScienceDirect, Springer and EMBASE were searched for articles published between 1 January 1995 and 20 June 2019. Articles that investigated the effects of occupational silica exposure on the risk of heart disease were considered.Study selection We included cohort studies, including prospective, retrospective and retroprospective studies.Data extraction and synthesis We extracted data using a piloted data collection form and conducted random-effects meta-analysis and exposure-response analysis. The meta-relative risk (meta-RR), a measure of the average ratio of heart disease rates in those with and without silica exposure, was used as an inverse variance-weighted average of relative risks from the individual studies. The Newcastle-Ottawa Quality Assessment Scale for cohort studies was used for study quality assessment.Outcome measure We calculated the risk of heart diseases such as pulmonary heart disease, ischaemic heart disease and others.Results Twenty cohort studies were included. The results suggest a significant increase in the risk of overall heart disease (meta-RR=1.08, 95% CI 1.03 to 1.13). Stronger evidence of association with pulmonary heart disease was found in the risk estimate of both categories of heart disease (meta-RR=1.24, 95% CI 1.08 to 1.43) and in the exposure-response analysis (meta-RR=1.39, 95% CI 1.19 to 1.62). Our subgroup analyses also revealed that the statistical heterogeneity among studies could be attributed mainly to the diversity in reference group, occupation and study quality score.Conclusions Silica-exposed workers are at an increased risk for overall heart disease, especially pulmonary heart disease. Further research is needed to better clarify the relationship between occupational silica exposure and ischaemic heart disease.PROSPERO registration number CRD42019124673.